Explaining changes in perceived wildfire risk related to the mountain pine beetle outbreak in north central Colorado - Hua Qin (Elsevier, 2021)
Longitudinal studies of risk perception, while growing, remain an understudied area of risk analysis research. Natural resource-based communities provide a key backdrop for analyzing dynamic risk perceptions and related social-ecological processes. Since the mid-1990s, a mountain pine beetle (MPB) outbreak has affected roughly 3.4 million acres of north central Colorado forests. Slow-moving landscape changes have taken place as a result of the outbreak, making it a relevant case study in which to examine wildfire and forest risk perceptions over time. In 2018, we replicated and expanded a 2007 mail survey of residents about local response to the MPB outbreak in nine north central Colorado communities. Using the initial and follow-up survey data from these study communities, we examined the changing wildfire risk perception and its relationships with various aspects of local human–nature interactions. The longitudinal surveys showed that perceptions of all forest risks except for forest fire and falling trees declined across the two study phases. Respondents in the 2018 survey also indicated increases in perceived likelihood of a wildfire, perceived severity of possible wildfire damage, and general concern about wildfire hazard. The analysis suggested that evolving wildfire risk perception was strongly associated with a number of explanatory variables and personal characteristics. Higher levels of perceived tree mortality, community interaction and communication, and individual actions in response to forest risks were consistently related to greater odds of indicating increased wildfire risk perception. In general, community social vulnerability, perceived tree re-growth, satisfaction with local management entities, and age were negatively related to the likelihood of having elevated perceptions of fire risk, whereas males and forest-related occupations were associated with relatively lower odds of reporting increases in perceived wildfire risk. Significant influencing factors for change also varied across the cognitive and affective dimensions of wildfire risk perception. Findings of this research have important implications for conceptual approaches, management and policy, as well as social-ecological indication and analysis in forest risk related areas.